Desenvolvimento de microcápsulas de camu-camu (Myrciaria dubia Mc Vaugh) obtidas pelo processo de gelificação iônica : estudo da estabilidade dos compostos bioativos - Santana, Geneluce Cruz Siqueira (2020)
Camu-camu (Myrciaria dubia (Mc Vaugh)) is an exotic fruit which presents high vitamin C content. Ion gelation is an encapsulation method which gives higher durability to the capsule and also protects its core against external environmental changes. It also helps to gradually realease the encapsulate compound. In this study, camu-camu juice microencapsulation produced more stable particles which promoted a protection to the fruit's bioactive compounds. The present work aimed to develop camu-camu microcapsules using the ionic gelation technique. It was used sodium alginate as a solidifying agent. It was also verified the bioactive compounds stability as well as the physical chemical and microbiological changes of P (control capsules) and S products (control capsules with addition of juice as a preservation medium) during storage at 5 ± 1C for 45 days in clear glass containers. Analyses were performed in duplicates and evaluated by Tukey test at a 5% significance level. The raw material used for processing was the camu-camu juice (solution with lyophilized fruit at 25% w / v) which differed (p˂0.05) from the microcapsules in most of the analyzed parameters. During the storage period, a more acidic product was detecetd, with a significant reduction in pH, retention of flavonoids levels (87%) and a content of 1,542.13 mg.100g-1 of vitamin C contributing to the antioxidant capacities, FRAP and DPPH. Carotenoids and phenolic compounds were gradually degraded. Regarding color, there was a loss of red tones with a slight increase in saturation and intensity. The addition of juice as a preservation medium in product S, differed significantly (5%) from product P only in the levels of flavonoids and vitamin C. There was no microbial contamination. FTIR spectra showed unusual compounds between the juice and the microcapsules, demonstrating the interaction which may occurred. Camu-camu microcapsule produced at this sutudy, showed a product with higher nutritional content which could be applicable in the formulation of innovative foods. It could also help in the prevention of various diseases and thus benefiting the health of consumers. It was concluded that its potential is promising!